Low tesla MRI in acute spinal injuries: a study in a teaching hospital - Nagvekar, Raghunath Anant; Nagvekar, Pooja (International Journal of Advances in Medicine, 2017)
Background: Early detection of spinal cord lesions in patients of suspected acute spinal injury leads to better prognosis. MRI has become a standard technique for evaluating spinal injuries and especially helpful for diagnosing acute compression of the spinal cord and cord oedema. This study was conducted to evaluate the low tesla MRI findings in cases of suspected acute spinal injuries. Methods: 120 patients with a suspected history of spinal injury who came into the emergency ward of our hospital were included into the study. MRI was done for all the patients within 2 days of admission. Results: The most common age group to be affected was 21-40 years with 48%followed by 41-60 years with 34% being affected. 46% of the patients had cervical injuries, 24% had dorsolumbar and lumbar injuries were seen in 17% of the patients. Spinal cord injuries was seen in 73 of the patients, out of which 64 patients had cord edema,7 with cord haemorrhage and 2 had cord transection. Conclusions: 0.3T MRI was able to identify cord compression and swelling, traumatic disc herniation’s, epidural hematoma, soft tissue injuries, and prevertebral/paravertebral hematoma, while MR imaging was unsatisfactory in identifying small fractures especially of posterior elements.